Prognostic value of intermediate age-related macular degeneration phenotypes for geographic atrophy progression. Issue 2 (8th April 2020) - Thiele, Sarah; Nadal, Jennifer; Pfau, Maximilian; Saßmannshausen, Marlene; Fleckenstein, Monika; Holz, Frank G; Schmid, Matthias; Schmitz-Valckenberg, Steffen
Abstract : Background: To characterise early stages of geographic atrophy (GA) development in age-related macular degeneration (AMD) and to determine the prognostic value of structural precursor lesions in eyes with intermediate (i) AMD on the subsequent GA progression. Methods: Structural precursor lesions for atrophic areas (lesion size at least 0.5 mm² in fundus autofluorescence images) were retrospectively identified based on multimodal imaging and evaluated for association with the subsequent GA enlargement rates (square-root transformed, sqrt). A linear mixed-effects model was used to account for the hierarchical nature of the data with a Tukey post hoc test to assess the impact of the local precursor on the subsequent GA progression rate. Results: A total of 39 eyes with GA of 34 patients with a mean age of 74.4±6.7 (±SD) years were included in this study. Five precursor lesions (phenotypes 1–5) preceding GA development were identified: large, sub-retinal pigment epithelial drusen (n=19), reticular pseudodrusen (RPD, n=10), refractile deposits (n=4), pigment epithelial detachment (n=4) and vitelliform lesions (n=2). Precursor lesions exhibited a significant association with the subsequent (sqrt) GA progression rates (p=0.0018) with RPD (phenotype 2) being associated with the fastest GA enlargement (2.29±0.52 (±SE) mm/year. Conclusions: The results indicate the prognostic relevance of iAMD phenotyping for subsequent GA progression highlighting the role of structural AMD features across different AMD stages.